Unusual and Rare Pneumocephalus Presentations in a Tertiary Care Center: Management Strategies and Review of Literature - Viswanathan, Rajanandhan; Sanjeevi, Venkatesan; Dhandapani, Balasubramanian (Indian Journal of Neurosurgery, 2020)
Pneumocephalus has various forms of presentations and a diverse etiology ranging from trauma to iatrogenic craniotomies and spinal surgeries. Most cases are benign and uncomplicated and resolve with minimal or no intervention. Few cases of pneumocephalus or pneumoventricles are either persistent despite treatment or present in various unique forms leading to considerable difficulty in the diagnosis and management of these patients. In this study, we analyze six cases of pneumocephalus with unusual and rare form of presentations and discuss their management strategies along with a review of relevant literature.
Keywords: pneumocephalus; pneumoventricles; management